Parenthèses et ruptures énonciatives en langue des signes française - Annie Risler (Discours)
How can parenthesis be defined in Sign Language? When applied to oral speech, the concept of parenthesis refers to a particular type of interpolated phrase, bounded on the left and on the right, and determined by prosodic, syntactic and discursive characteristics. The present work examines this particular type of enunciative discontinuity in French Sign Language (FSL). It highlights the existence of interpolated phrases in FSL, bounded on the left and on the right by various forms of syntactic “reactivation”, which are perfectly comparable to what is observed in vocal languages. Gaze and posture appear to be crucial markers of the spatial inscription of syntactic relations and of enunciative anchoring.